A reply to McLachlan. Issue 4 (August 1998) - Keown, John
Abstract : In an earlier article in this journal, I advanced five ethical arguments in favour of a voluntary, unpaid system of blood donation. In his reply to my article, Hugh McLachlan criticised one of those arguments, namely, the argument that an unpaid system promotes altruism and social solidarity. In this reply to Dr. McLachlan, I maintain that his criticism is misguided, and that he appears unclear not only about my own argument, but also about his own.